First club location and relative age as influences on being a professional australian rugby league player - Cobley, S.; Hanratty, M.; O'Connor, D.; Cotton, W. (International Journal of Sports Science and Coaching, 2014)
Bio-ecological systems theory suggests athlete development and success occurs via a complex inter-play of factors nested between and within individual, social context, and broader socio-cultural environments. On these predications, this study examined whether `first club location` and `relative age` independently and interactively affected the likelihood of becoming a professional Rugby League player. Data on 1509 Australian Rugby League professionals who played between 1998-2010 were obtained. Compared to population distributions, Chi-square and odds ratio analyses revealed a significant over-representation of players initiating their participation in small communities (i.e., < 20,000 residents), along with a contrasting under-representation from cities (i.e., > 1,000,000 residents). Professional players were also more likely to be relatively older (Q1 v Q4 OR = 1.80; CI = 1.47-2.21). A log-linear interactional analysis revealed no notable main trend (p < .07). However, the specific odds of a professional player being relatively older were reduced (OR = 0.68, CI = 0.50-0.92) when their first Rugby League club was in a small community (i.e., < 20,000 residents). Results highlight how characteristics of the social environment can potentially influence long-term patterns of athlete development and attainment in Australian Rugby League.